2020
DOI: 10.1080/13674676.2020.1767556
|View full text |Cite
|
Sign up to set email alerts
|

What helps young Christians grow in discipleship? Exploring connections between discipleship pathways and psychological type

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…How faith-based messaging influences marketplace discipleship is not well informed by empirical research. In their empirical study of nearly 300 Christian youth, Francis et al (2021) found group activities (e.g., participating in a group Bible study, prayer group, or Christian retreat) and individual experiences (e.g., studying the Bible, reading faith-based books and blogs, and spending time with mentors) strengthened the depth of discipleship. This research suggests continual immersion in the Word, through a combination of group and individual activities, is critical to disciples' growth.…”
Section: Witnessingmentioning
confidence: 99%
See 1 more Smart Citation
“…How faith-based messaging influences marketplace discipleship is not well informed by empirical research. In their empirical study of nearly 300 Christian youth, Francis et al (2021) found group activities (e.g., participating in a group Bible study, prayer group, or Christian retreat) and individual experiences (e.g., studying the Bible, reading faith-based books and blogs, and spending time with mentors) strengthened the depth of discipleship. This research suggests continual immersion in the Word, through a combination of group and individual activities, is critical to disciples' growth.…”
Section: Witnessingmentioning
confidence: 99%
“…LeTourneau, and Polydeck Screen Corporation provide some insights into how such group activities can be effectively integrated into companies' culture to encourage voluntary employee participation and enhance employees' discipleship (see Zigarelli, 2019). Executives may also consider making resources available (e.g., voluntary faith readings, corporate chaplains) for employees to engage in individual experiences similar to those found by Francis et al (2021) to enhance individuals' discipleship.…”
Section: Witnessingmentioning
confidence: 99%
“…Francis and Giordan (2021) report on a sample of 581 students enrolled in undergraduate sociology of religion course at Padua University, Italy, using the Italian version of the FPTS. Francis, Fawcett, et al (2021) report on a sample of 299 12-to 18-year-old Baptists attending a week-long summer programme of the Canadian Baptists of Atlantic Canada, Canada, using the Adolescent form of the FPTS (Fawcett et al, 2011). Shabtai (2021) reports on a sample of 16 Orthodox Jewish females using the FPTS.…”
Section: Introductionmentioning
confidence: 99%